Makna Kata dalam Kamus dan Makna Kata dalam Kalimat pada Terjemahan: Meaning of Words in The Dictionary and Meaning of Words in Sentences in Translation - Nuraeni Novira; Andi Abdul Hamzah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research aims to find out the meaning of words in the dictionary and the meaning of words in sentences in translation, it also aims to find out the types of semantic meaning or al-dilālah as well as the analysis of these semantic units. The type of research used in this case is library research (Literature Review). The data analysis technique used is descriptive analytical. The results of the research show 1) The meaning of words in the dictionary is called semantic science or al-dilālah. Vocabulary and Semantics are included in one science called lexicology, namely the science of mufradat or the science of al-mu'jam. 2) There are seven types of dilālah or meaning or semantics, including: Al-dilālah al-mu'jmaiyah/lexical meaning, al-Dilālah al-idhofiyah/additional meaning, al-dilālah al-nafsiyah, al-dilālah al-sautiyah/ phonological meaning, al-dilālah al-sarfiyah/ morphological meaning, al-dilālah al-nahwiyah/ grammatical meaning and al-dilālah al-ihaiyyah/ meaning of pronunciation elements. The division of al-wihdatu ad-dilaliyah is divided into four important parts, namely: single words, sentence structure/arrangement, bound morphemes, single sounds/phonemes